PENGARUH PEMAHAMAN WAJIB PAJAK, KUALITAS PELAYANAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA CIKARANG SELATAN - Marpaung, Uswatun Fadillah; Suhono; Suparno; Akbar.M, Nahruddien (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to examine and analyze the Effect of Taxpayer Understanding, Tax Service Quality and Tax Sanctions on Individual Taxpayer Compliance. The population in this study is individual taxpayers registered with KPP Pratama Cikarang Selatan. The determination of the number of samples in this study used the Slovin formula with a percentage error rate of 10%. with the number of samples used as many as 100 samples. The type of research applied to research is quantitative research through a descriptive approach. The data in this study uses primary data in the form of questionnaire distribution to individual taxpayers registered at KPP Pratama Cikarang Selatan who have income both employees / employees and entrepreneurs using Google forms that will be processed using the SPPS Version 25 program. The analytical methods used in this study are data quality test, classical assumption test, hypothesis test and multiple linear regression analysis. The results of this study show that Taxpayer Understanding, Tax Service Quality and Tax Sanctions simultaneously affect Individual Taxpayer Compliance. Viewed partially, Taxpayer Understanding and Tax Sanctions affect Individual Taxpayer Compliance. however, the Quality of Tax Services does not affect the Compliance of Individual Taxpayers. Thus, the better the understanding of taxpayers and tax sanctions will increase the compliance of individual taxpayers at the South Cikarang Pratama Tax Service Office, while the quality of tax services has not been able to fully improve the compliance of individual taxpayers